Physicochemical properties, antioxidant potential and mineral content of Miconia albicans (Sw.) Triana: a fruit with high aluminium content - Pasta, Paula Chiachia [UNESP]; Durigan, Giselda; Moraes, Izabel Cristina Freitas; Ribeiro, Leomara Floriano; Haminiuk, Charles Windson Isidoro; Branco, Ivanise Guilherme [UNESP] (Springer Nature, 2019)
A balanced and healthy diet entails the consumption of fruits since they are an important source of phytochemicals rich in vitamins–antioxidants. Therefore, identifying new fruits which can be included in the human diet is necessary. Miconia albicans (Sw.) Triana is a tall shrub native to the Brazilian savanna (“Cerrado”) that has not been consumed conventionally, but rather the vegetative material of this species has been widely recommended and consumed by humans as a part of traditional and herbal medicines. The fruits of M. albicans are consumed and dispersed by birds; however, previous studies have described bioaccumulation of aluminium in this species, which is reportedly toxic for humans. In order to evaluate the potential for human consumption of fruits from M. albicans, we characterized its physicochemical properties, including pH, moisture content, soluble solids, acidity, phenolic compounds, antioxidant capacity and mineral composition. We found high content of beneficial substances (calcium, zinc, magnesium, iron and antioxidants) in the fruits analysed. The aluminium concentration, however, is much higher than observed in other plants consumed by humans. The consumption of fruits M. albicans could impose potential risks of human health.
Keywords: Aluminium accumulation; Antioxidant capacity; Phenolic compounds; “Cerrado”